Brief Vigorous Stair Climbing Effectively Improves Cardiorespiratory Fitness in Patients With Coronary Artery Disease: A Randomized Trial - Dunford, Emily C.; Valentino, Sydney E.; Dubberley, Jonathan; Oikawa, Sara Y.; McGlory, Chris; Lonn, Eva; Jung, Mary E.; Gibala, Martin J.; Phillips, Stuart M.; MacDonald, Maureen J. (Frontiers in Sports and Active Living, 2021)
BACKGROUND: Cardiac rehabilitation exercise reduces the risk of secondary cardiovascular disease. Interval training is a time-efficient alternative to traditional cardiac rehabilitation exercise and stair climbing is an accessible means. We aimed to assess the effectiveness of a high-intensity interval stair climbing intervention on improving cardiorespiratory fitness (V̇O2peak) compared to standard cardiac rehabilitation care. METHODS: Twenty participants with coronary artery disease (61±7 y, 18 males, 2 females) were randomly assigned to either traditional moderate-intensity exercise (TRAD) or high-intensity interval stair climbing (STAIR). V̇O2peak was assessed at baseline, following 4 weeks of 6 supervised exercise sessions and after 8 weeks of ~24 unsupervised exercise sessions. TRAD involved a minimum of 30 min at 60-80 %HRpeak, and STAIR consisted of 3 bouts of 6 flights of 12 stairs at a self-selected vigorous intensity (~90s/bout) separated by recovery periods of walking (~90s). This study was registered as a clinical trial at clinicaltrials.gov (NCT03235674). RESULTS: Two participants could not complete the trial due to the time commitment of the testing visits, leaving n=9 in each group who completed the interventions without any adverse events. V̇O2peak increased after supervised and unsupervised training in comparison to baseline for both TRAD [baseline: 22.9±2.5, 4 weeks (supervised): 25.3±4.4 and 12 weeks (unsupervised): 26.5±4.8 mL/kg/min] and STAIR [baseline: 21.4±4.5, 4 weeks (supervised): 23.4±5.6 and 12 weeks (unsupervised): 25±6.2 mL/kg/min; p (time)=0.03]. During the first 4 weeks of training (supervised) the STAIR vs. TRAD group had a higher %HRpeak (101±1 vs 89±1%; p=≤0.001), across a shorter total exercise time (73.1±0.1 vs. 36.7±1.1 min; p=0.009). During the subsequent 8 weeks of unsupervised training, %HRpeak was not different (87±8 vs. 96±8%; p=0.055, mean±SD) between groups, however, the STAIR group continued to exercise for less time per session (10.0±3.2 vs. 24.2±17.0 min; p=0.036). CONCLUSIONS: Both brief, vigorous stair climbing, and traditional moderate-intensity exercise are effective in increasing V̇O2peak, in cardiac rehabilitation exercise programmes.